"The Shadow of Yesterday's Triumph": Pink Floyd's "Shine On" and the Stage Theory of Grief. (16th April 2018) - Cohen, Gilad
Abstract: The epic 1975 Pink Floyd song "Shine on You Crazy Diamond" was written, in part, as a requiem for the band's former leader, Syd Barrett, who suffered a mental breakdown. This article suggests that the musical structure of "Shine On" corresponds to the popular model of the five stages of grief: shock, yearning, anger, depression, and acceptance. Portraying the bereavement process of a band that had never recovered from the traumatic loss, this emotional arc imbues the piece with a powerful, genuine framework that demonstrates the band's propensity for evoking emotions through lyrics, composition, and meticulous arrangement and production.